2022
DOI: 10.1002/adma.202202714
|View full text |Cite
|
Sign up to set email alerts
|

Metalloid‐Cluster Ligands Enabling Stable and Active FeN4‐Ten Motifs for the Oxygen Reduction Reaction

Abstract: catalysts shown in Figure S18, Supporting Information, indicate that Te clusters remain stable during the electrocatalytic ORR reaction. These results demonstrate that FeN 4 -Te n may be competitive in various related electrochemical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 65 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…The prominent peaks at ≈25° and ≈43° in the XRD patterns were corresponding to the (002) and (101) facets of the pyrolyzed graphitic carbon, respectively, [3] which was further affirmed by the G‐band peaks at ≈1590 cm −1 in the Raman spectrum of Co 4 /Fe 1 @NC (Figure S16). It should be noted that no Co‐related metal peaks were observed in the XRD pattern of Co 4 /Fe 1 @NC, indicating the extremely small size of Co 4 ACs species, as also demonstrated in the previously reported literatures [9c, 17] . Interestingly, it was found that much richer pores were observed when the content of Co 4 MCs was gradually increased during the synthesis of Co 4 @NC (Figure S17a–c), which was probably caused by the Cl etching (from the ligands of Co 4 MCs) during the pyrolysis.…”
Section: Resultssupporting
confidence: 77%
“…The prominent peaks at ≈25° and ≈43° in the XRD patterns were corresponding to the (002) and (101) facets of the pyrolyzed graphitic carbon, respectively, [3] which was further affirmed by the G‐band peaks at ≈1590 cm −1 in the Raman spectrum of Co 4 /Fe 1 @NC (Figure S16). It should be noted that no Co‐related metal peaks were observed in the XRD pattern of Co 4 /Fe 1 @NC, indicating the extremely small size of Co 4 ACs species, as also demonstrated in the previously reported literatures [9c, 17] . Interestingly, it was found that much richer pores were observed when the content of Co 4 MCs was gradually increased during the synthesis of Co 4 @NC (Figure S17a–c), which was probably caused by the Cl etching (from the ligands of Co 4 MCs) during the pyrolysis.…”
Section: Resultssupporting
confidence: 77%
“…[ 23 ] Specifically, a shoulder peak at a larger bond distance (≈1.87 Å) originated from the Fe–P bonds, can be explicitly discriminated for Fe,P‐DAS@MPC. [ 4b,22a,24 ] Fe–Fe peaks at ≈2.18 and 2.56 Å observed in Fe foil and FeO are absent in Fe,P‐DAS@MPC, corroborating no Fe‐based clusters/nanoparticles are generated. Wavelet transformed (WT) EXAFS were then used to discern the contributions of each scattering pathway in both k and R spaces.…”
Section: Resultsmentioning
confidence: 67%
“…5f). [53][54][55][56][57][58][59][60][61][62][63][64] Long-term stability is directly associated with the practicability and effectiveness of the ZABs. The rechargeability and long-term cycling stability of ZABs were investigated to sustain 120 h (450 cycles) in 5 mA cm −2 (Fig.…”
Section: Resultsmentioning
confidence: 99%